MR Arthrography of the Shoulder: Technical Update and Clinical Applications - Sebro, Ronnie; Oliveira, Adriana; Palmer, William E. (Seminars in Musculoskeletal Radiology, 2014)
Direct MR arthrography of the shoulder is a safe, relatively easy procedure that can increase diagnostic confidence in the evaluation of rotator cuff and labroligamentous disorders compared with conventional MR imaging of the shoulder. Surgeons more often request MR arthrography in younger patients who may have internal impingement or subtle shoulder subluxation rather than obvious cuff rupture, repeated dislocation, or arthropathy. This article describes the advances in glenohumeral injection and MR protocol techniques, imaging pitfalls, anatomical variants, common lesions associated with internal derangement of the shoulder, and MR arthrography of the postoperative shoulder.
Keywords: magnetic resonance arthrography advances; shoulder; rotator cuff; labrum